The Functions of Principle as the Basis of Court Decision in Hard Cases - Peter Machmudz Marzuki (Yuridika, 2021)
The task of court is to produce just decisions. A court decision may be just if it coheres moral. Principle is praxis of moral. This article is to articulate that principle has significant meanings in court’s decisions. This is because principle is a moral standard that serves to be a reference for Court to settle hard cases equitably. In this writing, case approach is employed. In addition, it also uses comparative approach, in which court decisions of different countries are presented. The purpose of using comparative approach is to find similarities in referring to principle despite different jurisdictions and even different legal systems. From this study, it is found that principle may serve four functions to the court to reach equitable decisions. First, it may be a legal basis for the court to settle a case equitably in the absence of legal rule. In fact, not all human conducts are prescribed by law. It is frequently presumed that what is not prohibited is permitted to do. In this study, it is found that what is not forbidden is not necessarily permissible. The corner stone of determining whether or not it is permissible is principle. In this case, principle served to be legal basis directly applied by the court to avoid producing unjust judgment. Second, the principle has the derogatory function to supersede a statutory provision. In this case, applying such a provision may result in decision contrary to moral. This, certainly, contradicts the idea of the establishment of court of justice. It is justified, therefore, referring to the principle, the court supersedes such a statutory provision to bring about a just decision. Third, the principle serves to be a basis for the court to interpret obscure statutory provision governing the case. It is not unusual that statutory provision is obscure or ambiguous. Such a provision is hard to understand. Settling the case governed by such a provision appropriately, the court should interpret the provision sensibly.